Law of Torts-concept & application: occupier's liability (OL) - Ismail, Suzi Fadhilah (2015)
Slides presented for Law of Torts Concept & Application Course- Occupier's Liability, held at Malaysia Anti-Corruption Academy (MACA), Kuala Lumpur from 17-19th November 2015.